Effect of droplet diameter and global equivalence ratio on n-heptane spray auto-ignition. (1st January 2017) - Zhou, Taotao; Ye, Taohong; Zhu, Minming; Zhao, Majie; Chen, Jing
Graphical abstract: The temporal evolution of joint PDF of the mixture fraction and scalar dissipation rate is a key parameter relating to the happening of ignition. Highlights: Three-dimensional DNS with complex chemistry are carried out. General evolution of the ignition process is investigated. Effect of droplet diameter and global equivalence ratio is studied. Joint PDF of η and χ is a key parameter for ignition delay. Abstract: Three dimensional DNS are performed to investigate the auto-ignition behavior of n -heptane droplets in high-temperature products of premixed H2 /air combustion. A skeletal chemistry which contains 44 species 122 element reactions is adopted. Two-way coupling is considered for the interaction between liquid phase and gas phase by Eulerian-Lagrangian point-source approach. The initial turbulence is homogenous and isotropic. Five cases of diverse initial droplet size and global equivalence ratio are carried out to study their effects on the ignition process. The most reactive mixture fraction η MR is determined. The statistical characteristics of mixture fraction η and the scalar dissipation rate χ are examined, in terms of the probability density function (PDF) P ( η ) and conditional averaged dissipation rate 〈χ| η 〉 respectively. The temporal evolution of joint PDF of η and χ at the point ( η = η MR, χ = 0) is analyzed. It is found that P ( η MR, χ = 0 ) is a key parameter relating to the happening of ignition.